2014
DOI: 10.2144/000114187
|View full text |Cite
|
Sign up to set email alerts
|

P-LinK: A Method for Generating Multicomponent Cytochrome P450 Fusions with Variable Linker Length

Abstract: Fusion protein construction is a widely employed biochemical technique, especially when it comes to multi-component enzymes such as cytochrome P450s. Here we describe a novel method for generating fusion proteins with variable linker lengths, protein fusion with variable linker insertion (P-LinK), which was validated by fusing P450cin monooxygenase (CinA) to the flavodoxin shuttle protein (CinC). CinC was fused to the C terminus of CinA through a series of 16 amino acid linkers of different lengths in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…In another study, in which a P450 was fused to a flavodoxin shuttle protein, a library of linkers was designed, ranging from one to 16 amino acids. The variants were compared based on whole‐cell conversion, and the optimal linker was found to contain ten amino acids . Strong differences were also found in a β‐glucanase–xylanase fusion with different linker lengths, with greatly improved activities for both enzyme activities .…”
Section: Fusion Design and Linker Designmentioning
confidence: 99%
“…In another study, in which a P450 was fused to a flavodoxin shuttle protein, a library of linkers was designed, ranging from one to 16 amino acids. The variants were compared based on whole‐cell conversion, and the optimal linker was found to contain ten amino acids . Strong differences were also found in a β‐glucanase–xylanase fusion with different linker lengths, with greatly improved activities for both enzyme activities .…”
Section: Fusion Design and Linker Designmentioning
confidence: 99%
“…In this way, improvements in expression rates, activities and coupling have been observed. The impact of fusing the reductase and haem domain, however, was smaller than expected . To improve the efficiency of P450s for whole cell applications, several aspects have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach towards linker length variation was used by Schwaneberg and colleagues . They studied the influence of the linker length between the P450cin monooxygenase (CinA) and the flavodoxin shuttle protein (CinC), whereas the reductase (Fpr) remained in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that Baeyer–Villiger monooxygenases could be genetically fused with NADP + reductases, which simplified cofactor regeneration . Ferrodoxin and flavodoxin reductase‐type domains could also be fused to cytochrome P450 heme domains to generate self‐sufficient hydroxylation catalysts . We therefore envisioned that an FDH‐FR fusion enzyme could be useful for a wide range of in vitro and in vivo applications.…”
Section: Methodsmentioning
confidence: 99%
“…The genes encoding wild‐type RebH and RebF were genetically fused by using three linkers based on sequences used to create the functional P450‐reductase fusion enzymes noted above . These linkers consisted of 10, 16, and 22 residues (Figure A), and the corresponding fusion enzymes are referred to as H‐10‐F, H‐16‐F, and H‐22‐F.…”
Section: Methodsmentioning
confidence: 99%